EP 145. Neuropeptide Y and the cellular effects of transcranial magnetic theta-burst stimulation in rat neocortex. Issue 9 (September 2016) - Jazmati, D.; Neubacher, U.; Aliane, V.; Funke, K.
Abstract : Questions: High-frequency transcranial magnetic stimulation with theta-burst stimulation (TBS) induces strong and highly synchronous cortical network activity principally able to trigger epileptiform activity or to cause over-excitation of distinct neurons. Our previous studies showed that intermittent TBS (iTBS) strongly reduces the expression of the calcium-binding protein parvalbumin (PV) in fast-spiking inhibitory interneurons (FSI). Since PV is expressed in an activity-dependent manner, strong activation of these neurons during iTBS might have triggered mechanisms to prevent permanent over-excitation. One well-described process is the reduction of glutamate release from excitatory terminals targeting FSI via the action of neuropeptide Y (NPY). Therefore, we first tested if iTBS increases the expression of NPY in rat cortex and second, if application of NPY to the lateral ventricle can counteract the cortical iTBS effect of reducing PV expression. Methods: In the first study, frontal sections of rat brains previously treated with one to five blocks of iTBS (600 pulses per block, intervals of 15 min) were immunostained for NPY and PV. In the second study, rats received either 20 μ l NPY (24 nMol) or methylene blue as a control (MB) via intracranial injection to the left lateral ventricle (2 μ l/min) followed 60 min later by either verum or sham iTBS (3 blocks @ 15 min = 1800 pulses). Further 60 min later rats were perfused for PV immunostaining of their brains. Results: iTBS gradually increased the number of NPY+ neurons in a dose-dependent fashion from about 60 cells/mm 2 to about 130 cells/mm 2 after five iTBS blocks. The same stimulation protocol was previously found to decrease the number of PV+ neurons by about 40% after five iTBS blocks (Volz et al., Brain Stimulation 2013). NPY injected into the lateral ventricle of the left forebrain (no diffusion to the right hemisphere) prevented the reduction of PV+ cells (−40%) by iTBS in the left but not in the right hemisphere and further increased the number of PV+ cells. A slight increase in PV+ cells was also evident in sham stimulated animals when comparing NPY with MB injections. Conclusions: As expected, iTBS increased the expression of NPY likely due to the strong and highly synchronous activation of cortical networks. Since strong excitation is especially harmful to FSI, the reduction in PV expression indicates a post-stimulation depression of excitatory inputs and subsequent hypoactivity of these interneurons. The finding that NPY prevents the strong reduction in PV expression indicates that it is able to prevent over-excitation of FSI. This study has been supported by grants of the Deutsche Forschungsgemeinschaft (DFG): SFB 874 TP A4 and the Federal Ministry of Education and Research (BMBF): GCBS-WP1_Bochum (01EE1403B) to K. Funke.